Zur Verbreitung der Arten der Formica rufa Linnaeus-Gruppe. I. Häufigkeit, geographische Verteilung und Vorzugsstandorte der Roten Waldameisen im Gebiet der Deutschen Demokratischen Republik (Hymenoptera: Formicidae). - Otto, Dieter (Contributions to Entomology = Beiträge zur Entomologie, 1968)
The following hill-building species of Formica are to be found in the woods of the German Democratic Republic: F. polyctena Foerster, F. rufa Linnaeus, F. pratensis Retzius, F. truncorum Fabricius, F. (Raptiformica) sanguinea Latreille and F. (Coptoformica) exsecta Nylander. With an average density of only 2.5 to 5.8 nests per 100 hectares wooded area, the ant population is in general rather thin. About half of the colonies belong to the species F. polyctena. Data about favourite regions, biotopes and habitats, about ecological requirements and biological properties are given for some of the most important species.